The mysterious Benedict Society and the perilous journey - Stewart, Trenton Lee.; Sudyka, Diana (Boston : Little, Brown, 2008)
Reynie, Kate, Sticky, and Constance, all graduates of the Learning Institute for the Very Enlightened and members of the Benedict Society, embark on a scavenger hunt that turns into a desperate search for the missing Mr. Benedict.
School Library Journal
School Library Journal starred
Wilson's Junior High School
Booklist, March 2008
Bulletin (Center for Children's books), July 2008
Christian Library, October 2010
Keywords: Missing persons -- Juvenile fiction; Treasure hunt (Game) -- Juvenile fiction; Adventure and adventurers -- Fiction; Missing persons -- Fiction; Missing persons -- Fiction; Science fiction; Science fiction; Treasure hunt (Game) -- Fiction; Treasure hunt (Game) -- Fiction; Adventure fiction; Missing persons -- Fiction; Science fiction; Treasure hunt (Game) -- Fiction; Adventure fiction; Science fiction